PENERAPAN METODE TIME DRIVEN ACTIVITY BASED COSTING (TDABC) DALAM PERHITUNGAN KOS SERVICE PADA BENGKEL HBBA - Mira Ely; Rochman Effendi; Imam Mas'ud (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2019)
The purpose of this research is to know the process of calculation cost of service on HBBA Automotive Repair shop using Time Driven Activity Based Costing (TDABC) method. This research was conducted in one of Member's HBBA that is Formula Automotive Repair shop. This type research is qualitative research. Data collection methods used ini this research are observation, interview and documentation. Data analysis method used in this research is descriptive analytical. The result of this research showed when Formula Automotive use Time Driven Activity Based Costing (TDABC) method in determining cost of service is more clear and appropriate in accordance with utilization available resources in each services. Which is different with whats done by the company in determining cost of service, where the company still has not made a definite calculation and this can be seen when determining price of service based on provisions of owner and mechanics still using estimates. The results of calculation of Time Driven Activity Based Costing (TDABC) method there are 3 types of services that have a cost that is too large compared to the service price determined by Formula Automotive Repair shop, namely wheel laher replacement, ac service and lamp service. So it is necessary to determine new price of service. Keywords: Cost of Service, Price of Service, Time-Driven-Activity Based-Costing